A new therapeutic approach in Gorham–Stout disease: a case report - Stawarz, Katarzyna; Galazka, Adam; Kissin, Filip; Zwolinski, Jakub (Frontiers in Surgery, 2023)
Gorham -Stout disease is a rare condition of unknown prevalence and unknown exact cause. Its pathogenesis is based on enhanced osteoclastic activity leading to bone resorption and bone replacement by distended lymphatic vessels. Because of its rarity and a various range of symptoms the disease may give, it is a challenging diagnosis and a strong index of suspicion is required. Although it is a benign condition, the prognosis may be unpredictable. The treatment options suggested so far are limited and every case should be provided with the best individual approach. Herein, we present a case report of Gorham -Stout disease managed with a regular lump drainage with a good response and control of the patient symptoms over a period of 20 years.A 23-year old men was admitted to the Head and Neck Cancer Clinic with a six month history of a left-sided neck lump. Other symptoms reported were neck pain and general weakness. The basic laboratory tests were within normal limits. On physical examination a large round lump on the left side of a patient!s neck and left armpit were noticed. They were about several centimeters in diameter, soft on palpation but firmly attached to underlaying tissue. The CT scan ordered revealed large lymphatic left-sided masses of the neck and axillary fossa and multiple osteolytic lesions in the patient!s vertebrae. Together with the biopsy findings and imaging studies a diagnosis of Gorham -Stout Syndrome was made. The patient was then scheduled for a regular cystic drainage with good control of a disease for over a period of 20 years.The Gorham -Stout disease is a rare challenging condition and the available treatment options remain sparse. Surgical approach although effective is not always possible. Besides, the risk of radiotherapy induced malignancy causes that this therapy may eventually result in unfavorable response. Depending on symptoms and the disease location, this condition requires an individual treatment plan. The presented case illustrates that minimal invasive approach may result in a good control of the Gorham -Stout syndrome and may stand as an alternative treatment option for some patients with this condition.